An examination of substance use trends among adolescents receiving mental health treatment in Ontario - Stewart, Shannon L.; Drew, Abbey L.; Fearon, Danielle (Frontiers in Psychiatry, 2025)
IntroductionAdolescent substance use continues to pose a significant public health concern due to its well-documented adverse effects on long-term health and well-being. Various risk factors, including mental health concerns (e.g., anxiety, depression), residential instability, prenatal exposure to substances, and various psychosocial concerns (e.g., low self-concept, poor social skills), have been recognized as contributors to adolescent substance use. Given the complex nature of substance use, it is essential to better our understanding of the factors that contribute to it.MethodsThe current study aims to explore substance use trends among Ontario adolescents and examine the contexts in which these behaviors emerge. This study uses data from the interRAI Child and Youth Mental Health (ChYMH) assessment instrument, collected from youth receiving mental health services in Ontario between 2012 and 2022. Hierarchical logistic regression analysis was used to identify factors associated with triggering the Substance Use CAP.ResultsIn our sample, females, and older youth (15-18) were most likely to engage in substance use. Results indicated that residential instability, living alone or in a shelter, and living with a single parent are associated with substance use in adolescents. Furthermore, findings revealed that past or recent trauma, internalizing behavior, and school disengagement increased likelihood of engaging in substance use.Discussion and implicationsThis research provides researchers and clinicians with important insights into risk factors for substance use among adolescents which can be used to inform care planning and the development of prevention and early intervention efforts.